Psychological Features of Hypnotizability: A First Step Towards Its Empirical Definition. Issue 1 (2nd January 2017) - Facco, Enrico; Testoni, Ines; Ronconi, Lucia; Casiglia, Edoardo; Zanette, Gastone; Spiegel, David
Abstract: This study examined the relationship between the Hypnotic Induction Profile (HIP) and several psychological tests: Tellegen Absorption Scale (TAS), Spontaneity Assessment Inventory-Revised (SAI-R), Dissociative Experiences Scale (DES), Short-Form Boundary Questionnaire (SFBQ), Mini Locus of Control (MLOC), Testoni Death Representation Scale (TDRS), and the Interpersonal Reactivity Index (IRI). Two hundred and forty volunteers were administered the above tests; 78 of them were also administered the HIP, and its scores were compared to those on the other tests. A significant correlation was found among the TAS, DES, SFBQ, and IRI. The HIP was significantly correlated to the DES ( r  = .19 p 1tail  = .045), and the IRI-ec subscale ( r  = .19 p 1tail  = .044); 14 test items from DES, IRI, TAS, SAIR, and SFBQ were also significantly related to the HIP. The findings suggest that hypnotizability may relate to stronger perception of the inner world, decreased aptitude for managing memory processing, and increased sensitivity and empathy.